In Vitro Assessment with the Infrared Thermometer of Temperature Differences Generated During Implant Site Preparation: The Traditional Technique Versus the Single‐Drill Technique. (17th July 2014) - Lucchiari, Nicola; Frigo, Anna Chiara; Stellini, Edoardo; Coppe, Matteo; Berengo, Mario; Bacci, Christian
Abstract: Purpose: To assess in vitro, using an infrared (IR) thermometer, temperature changes generated at implant sites by osteotomies involving two different drilling methods (with multiple drills versus only one) and to measure the influence of irrigation on the temperature variation. Materials and Methods: Forty bone samples (from bovine rib) were divided into two groups of 20. Osteotomies were performed in group A with four drills, using the standard method (Leone Dental Implant System, final diameter 3.5 mm), and in group B with a single drill (Zero1 Drill, Leone Dental Implant System 3.5 mm diameter). In each group, half of the osteotomies were performed with irrigation (subgroups A1 and B1) and the other half without irrigation (subgroups A2 and B2). Two osteotomies were performed on each sample, using four different‐sized drills according to the standard technique on one side and using a single drill on the other side. The starting temperature ( T 0 ) and the maximum temperature ( T max ) reached in the bone were measured. Comparisons of ΔT were drawn between subgroups A1 and B1 and between subgroups A2 and B2. The data were analyzed using Student's t ‐test (with 95% confidence interval). Results: The mean difference identified between the temperature produced with the last drill used in the traditional technique and that produced with the single drill was 0.3150 ± 1.0194°C when irrigation was used (group A1 vs group B1; not statistically significant). The mean difference between the temperature produced with the last drill of the traditional technique and that produced with the single drill was −0.3526 ± 0.5232°C when irrigation was not used (group A2 vs group B2; statistically significant). Conclusions: The single‐drill method induced a significantly greater variation in temperature than the traditional method, but only when irrigation was used; without any irrigation, the difference in the temperature variation generated by the two methods was not statistically significant. In any case, bone heating during the osteotomy never exceeded 2°C and was clinically irrelevant, as thermal damage to bone has only been reported in the literature for temperatures beyond 47°C persisting for more than one minute.